2000
DOI: 10.1016/s1526-9523(00)00019-2
|View full text |Cite
|
Sign up to set email alerts
|

Against the Odds: Breastfeeding Experiences of Low Income Mothers

Abstract: This qualitative study asked low income mothers about their experiences of breastfeeding care in the health system and about integrating breastfeeding into their daily lives. Focus group interviews were conducted with urban and rural nursing mothers who participated in the WIC Program and were supported by breastfeeding peer counselors. Mothers said that helpful breastfeeding care providers knew correct information, established supportive personal relationships, referred women to breastfeeding specialists for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
131
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(136 citation statements)
references
References 25 publications
5
131
0
Order By: Relevance
“…Also, breastfeeding initiation increased nearly 5-fold among black women and nearly 11-fold among single women. Raisler et al 34 found similar results from focus group interviews with low-income mothers who reported that the personal contact with a health care provider was more effective than written information or videos.…”
Section: Figurementioning
confidence: 76%
“…Also, breastfeeding initiation increased nearly 5-fold among black women and nearly 11-fold among single women. Raisler et al 34 found similar results from focus group interviews with low-income mothers who reported that the personal contact with a health care provider was more effective than written information or videos.…”
Section: Figurementioning
confidence: 76%
“…Results are consistent with previous research indicating that African American mothers often experienced differences in care from breastfeeding support professionals in ways that undermine and discourage their breastfeeding behavior. 19,50 These findings have implications for training healthcare providers to provide culturally appropriate care for increasingly diverse populations of mothers in ways that assure consistency and avoid racial bias in breastfeeding education.…”
Section: Local Implementation Of Institutional-level Interventions Anmentioning
confidence: 99%
“…The reasons low-income women in general do not breastfeed and instead choose formula include the belief that breastfeeding is painful, the lack of a supportive environment, embarrassment about nursing in public, concern that breastfeeding is restrictive and inconvenient, and the need to return to work or school (Raisler, 2000). Women who initiate breastfeeding, but wean prematurely, often do so because of perceived inadequate milk supply, maternal fatigue, and sore nipples (Milligan, Pugh, Bronner, Spatz, & Brown, 2000).…”
Section: Breastfeeding Choices Of Low-income Mothersmentioning
confidence: 99%